Treating Consumption: How the Social Costs of Chain Stores Affect Consumers. Issue 3 (3rd July 2021) - Dellora, Carlo
Abstract: This work sets out to consider the effects of consumption from a new angle. While much has been written about the economic and political implications of chain stores, little has been devoted to their social costs on consumers. Focusing on the American experience, this work argues that such stores take an unquantifiable toll on those who use their services that often goes unnoticed. The terminology developed by Kapp of "social costs, " is adopted here to describe the effects of these stores on their consumers. These social costs, it is argued, must be factored in to the prevailing—consequentialist—economic assessment of chain stores that highlights their reduced prices and increased range. Any properly consequentialist account of such stores must consider other costs alongside these economic benefits before accepting the merits of chain stores and their proliferation.